Libyan cancer patients at King Hussein Cancer Center for more than a decade, the current situation, and a future vision - Erashdi, Madiha; Al-Ani, Abdallah; Mansour, Asem; Al-Hussaini, Maysa (Frontiers in Oncology, 2023)
Background: Since 2011, the Libyan civil war crisis had affected all dimensions of livelihood including cancer care. This has resulted in a steady incline in the number of Libyan patients with cancer seeking oncologic care and management in Tunisia, Egypt and Jordan, among others. King Hussein Cancer Center (KHCC) been one of the main destinations for Libyan patients with cancer for over more than a decade. Aim: We are reporting on the characteristics of Libyan patients with cancer presenting to KHCC during the past thirteen years. Methods: We performed a retrospective chart review of all Libyan patients with cancer presenting to KHCC between 2006 and 2019. Results: A total of 3170 records were included in the final analysis. The overall sample were predominantly adults (71%) with male-to-female ration of 1:1.2. Overall, the most common referred cancers to KHCC were breast (21%), hematolymphoid (HL) (17%), and gastrointestinal tract (GIT) (16.2%) cancers. Breast cancer was the most common among adult females (41.7%), GIT among adult males (23.6%), and HL among pediatrics (38.5%). Around 37.8% of patients presented with distant metastasis at their first encounter at KHCC, among which 14.7% were candidates for palliative care. Conclusion: The sustenance of treatment for Libyan patients with cancer requires extensive collaboration between governmental and private sectors. The Libyan oncological landscape could benefit from national screening programs, twining programs, introduction of multidisciplinary boards, and the formulation of a national cancer registry. Adopting the successful models at KHCC can help to augment the oncology services within the Libyan healthcare sector.